4. OVERVIEW OF CUPPING METHOD IN TRADITIONAL MEDICINE (Vietnam Journal of Community Medicine, 2024)
Non-drug treatment methods according to Traditional Medicine are increasingly widely used in the treatment of many different diseases and disorders, including cupping therapy. Cupping is beneficial for general health and effectively solves a number of local and systemic diseases. Dry and wet cupping techniques can be applied to effectively relieve musculoskeletal pain. However, dry cupping was often preferred because it has a significantly lower risk of blood exposure, making it a safer option for practitioners and patients. However, studies was indicated that wet cupping may be beneficial for systemic disorders, including obesity-related conditions, autoimmune and inflammatory diseases, psychiatric disorders, skin conditions,…
Keywords: traitional medicine; cupping; dry cupping; wet cupping